On the stability of river bifurcations created by longitudinal training walls. Numerical investigation. (March 2018) - Le, T.B.; Crosato, A.; Mosselman, E.; Uijttewaal, W.S.J.
Highlights: Parallel channels separated by a wall tend to be unstable in rivers with steady bars. The start of the wall with respect to a steady bar governs bifurcation stability. Simulations suggest that careful design can limit bifurcating channel instability. Abstract: To maintain a navigable channel and improve high-flow conveyance, engineers have recently proposed constructing longitudinal training walls as an alternative to the traditional transverse groynes. However, previous work has shown that the system of parallel channels created by a longitudinal training wall might be unstable in rivers with alternate bars. Many questions remain unanswered, particularly whether a stable system can be obtained by carefully designing the bifurcation point. This work analyses the stability of the bifurcating system created by a thin longitudinal wall in sand-bed rivers with alternate bars or point bars. The methodology includes performing 102 numerical tests using the Delft3D code to reproduce an idealized low-land river, either straight or meandering. The results show that the system of parallel channels separated by a training wall may indeed become unstable. An important factor is found to be the location of the bifurcation point with respect to a neighboring bar or point bar. The same trends are observed for both constant and variable discharge, in straight and meandering channels. The results suggest that cyclic growth and decline of the bifurcating channels may arise as inherent system behavior, without the need of any additional external forcing. We explain this from changes in the relationship between sediment transport ratio and discharge ratio as the bifurcation evolves. This cyclic behavior can be regarded as a form of system stability and can be obtained by carefully placing the starting point of the longitudinal training wall, and thus the bifurcation point, near the top of a bar.